Measuring attraction to screen devices in early childhood: development of the Affinity-TV and Affinity-Mobile scales - Thompson, Darcy A.; Kaizer, Laura K.; Schmiege, Sarah J.; Cabrera, Natasha J.; Clark, Lauren; Ringwood, Haley; Miramontes Valdes, Estefania; Tschann, Jeanne M. (Frontiers in Pediatrics, 2025)
IntroductionWith the increasing integration of digital screen devices into our everyday life, there has been increased attention regarding the risk of “problematic” use or pathological use. Because children start using screen devices in the first few years of life, early identification of those at risk for future problematic use could inform early prevention efforts. Children's attraction to screen devices in early childhood may identify those at risk for future problematic use; however currently, there are no measures of toddlers' attraction or affinity to screen devices. The objective of this study was to develop survey measures of toddler affinity to screen media, inclusive of televisions, smartphones, and tablets.MethodsMeasures were developed using an exploratory sequential mixed methods (qualitative -> quantitative) approach. Participants were Mexican American mothers of toddlers 15–26 months old. Findings from semi-structured interviews were used to develop items reflecting parental reports of child affinity to screen devices. Items were administered by phone to 384 mothers. Analyses included evaluation of the factor structure and psychometric properties of Affinity-TV (10 items) and Affinity-Mobile (12 items), and evaluations of correlations between each scale with social emotional outcomes and demographic characteristics.ResultsFactor analysis supported a one-factor solution for each scale. Reliabilities were acceptable for both scales (Cronbach's alpha > .75). There was a significant positive correlation between Affinity-TV and Affinity-Mobile (rs = 0.44, p < 0.001). Affinity-TV was significantly positively correlated with toddler average daily minutes of TV use (rs = 0.27, p < 0.001) and average daily minutes of mobile use (rs = 0.10, p < 0.05). Affinity-Mobile was significantly positively correlated with toddler average daily minutes of mobile use (rs = 0.31, p < 0.001), but not with average daily minutes of TV (rs = −0.04, NS). Each scale was correlated with social emotional developmental outcomes.DiscussionThe Affinity-TV and Affinity-Mobile scales have good initial reliability and adequate predictive validity. These findings support the use of Affinity-TV and Affinity-Mobile in toddlers as measures of children's attraction to screen devices. These measures may help to identify early risk for problematic use, and they offer a novel way to evaluate a child's behavioral reaction to screen devices in early childhood.